The Ik language: Dictionary and Grammar Sketch - Schrock, Terrill (My University, 2017)
This book is a dictionary and grammar sketch of Icétôd (Ik), one of the three Kuliak languages spoken in northeastern Uganda, in the Karamoja region. It is the lexical sequel to A grammar of Ik (Icé-tód): Northeast Uganda’s last thriving Kuliak language (Schrock 2014). This volume includes an Icétôd-English dictionary with roughly 8,700 entries, followed by a reversed English-Icétôd index. This is then supplemented with a sketch of Icétôd grammar that is nearly comprehensive in its coverage of topics and is written in a simple style, using standard linguistic terminology, but in a way that is accessible to non-linguists. As a whole, this book may be useful for language and curriculum development for the Ik people, as a reference for non-Ik language-learners, and as a source of data not only for the comparative study of Kuliak but also the Afroasiatic and Nilo-Saharan language families.
Keywords: Ik language; Dictionary; grammar sketch